Truncation of Cas9 protein for high performance target-specific genome engineering - Wang, Fei (2017)
Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR associated proteins (Cas) system has emerged as a genome engineering tool with the programmable guide RNA sequence for specific gene targeting. However, for lentiviral based in vivo testing and engineering such as adeno-associated viral (AAV) vectors, the size of the protein like Streptococcus pyogenes Cas9 (SpCas9) was larger than vector capacity, and the transduction efficiency is lowered if more vectors were used. In this project, nuclease-null Cas9 fused with VP64-p65-Rta (Sp-dCas9-VPR) was managed to be truncated at various regions, and with a 527-amino acid deletion, the protein was able to retain ~40% of the wildtype activity as a transcriptional activation factor, and the same rationale was applied to other Cas proteins for smaller protein with high performance.